2009
DOI: 10.4269/ajtmh.2009.09-0150
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic Profiles of Artesunate After Single Intravenous Doses at 0.5, 1, 2, 4, and 8 mg/kg in Healthy Volunteers: A Phase I Study

Abstract: Abstract. The pharmacokinetics of good manufacturing process injection of artesunate (AS) were evaluated after single doses at 0.5, 1, 2, 4, and 8 mg/kg with a 2-minute infusion in 40 healthy subjects. Drug concentrations were analyzed by validated liquid chromatography and mass spectrometry system (LC-MS/MS) procedures. The drug was immediately converted to dihydroartemisinin (DHA), with elimination half-lives ranging 0.12-0.24 and 1.15-2.37 hours for AS and DHA, respectively. Pharmacokinetic model-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
44
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 27 publications
(30 reference statements)
11
44
0
Order By: Relevance
“…We have shown that artesunate inhibits the replication of JCPyV in COS-7 cells with an EC 50 of 2.9 M, a concentration that can be achieved in plasma (60)(61)(62). However, to be eligible for therapeutic treatment for PML, artesunate also needs to cross the blood-brain barrier and enter the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that artesunate inhibits the replication of JCPyV in COS-7 cells with an EC 50 of 2.9 M, a concentration that can be achieved in plasma (60)(61)(62). However, to be eligible for therapeutic treatment for PML, artesunate also needs to cross the blood-brain barrier and enter the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Oral data presented here contrast with recently reported intravenous (i.v.) data for good manufacturing process (GMP) intravenous artesunate, which found not only rapid hydrolysis of AS to DHA but also much higher C max values for AS than for DHA (22). The comparison suggests high first pass metabolism of AS when given by the oral route.…”
Section: Figmentioning
confidence: 97%
“…However, to inhibit the replication of BKV in RPTECs by 50% (i.e., the EC 50 ), a concentration of 4.2 M (1.6 g/ml) artesunate was needed, and it is still unclear if this concentration can be attained in kidney epithelial cells in vivo. Following intravenous administration of artesunate in healthy volunteers, plasma concentrations up to 217 M (83.34 g/ml) have been described (29,53,54), indicating that the EC 50 could at least be achieved in the plasma.…”
Section: Discussionmentioning
confidence: 99%